2016
DOI: 10.1142/s2010135x16500326
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electrical properties of BaBiO3 and high resistivity BaTiO3–BaBiO3 ceramics

Abstract: Ceramics of the composition BaBiO 3 (BB) were sintered in oxygen to obtain a single phase with monoclinic I2/m symmetry as suggested by high-resolution X-ray diffraction. X-ray photoelectron spectroscopy confirmed the presence of bismuth in two valence states -3þ and 5þ. Optical spectroscopy showed presence of a direct bandgap at $ 2.2 eV and a possible indirect bandgap at $ 0.9 eV. This combined with determination of the activation energy for conduction of 0.25 eV, as obtained from ac impedance spectroscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…The edge energy of 25BZT was found to be very similar to Bi 2 O 3 , with no noticeable shift to higher energy values, and the pre‐edge bump was also absent. Thus, there was no evidence of Bi 5+ in 25BZT ceramics, within the resolution of the instruments used.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The edge energy of 25BZT was found to be very similar to Bi 2 O 3 , with no noticeable shift to higher energy values, and the pre‐edge bump was also absent. Thus, there was no evidence of Bi 5+ in 25BZT ceramics, within the resolution of the instruments used.…”
Section: Resultsmentioning
confidence: 81%
“…In separate reports on macroscopic transport properties, it was shown that on forming solid solutions with small amounts of Bi M O 3 to BT, their insulation properties improve by multiple orders of magnitude. There is also a corresponding transition from p‐type behavior for BT towards n‐type for BT‐Bi M O 3 ceramics without any deliberate donor doping, indicating a drastic change in underlying defect equilibrium conditions . A thorough study of the complex defect mechanisms in BT‐Bi M O 3 has been performed in this article, which intends to explain the observed change in transport properties on adding Bi‐perovskites to BT.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The past two decades have witnessed a significant renaissance of the bismuthate BaBiO 3 from both a technological and scientific viewpoint [1][2][3][4][5][6][7][8][9][10][11], especially as a superconductor [1,3,[5][6][7] because of its electronic properties, and as a promising photocatalyst toward the degradation of organic pollutants [2], water splitting [9,10], CO 2 reduction [4], and as a prospective photovoltaic material [11]. The unique properties of BaBiO 3 are largely the result of the occurrence of both Bi 3+ and Bi 5+ oxidation states that have tended to complicate studies of this bismuthate.…”
Section: Introductionmentioning
confidence: 99%
“…Their comparison of the photoemission, optical absorption, and transport data on BaBiO 3 suggested the existence of polaron energy levels within the bandgap of BaBiO 3 that accommodate thermally excited charge carriers. Kumar and coworkers [5] synthesized this bismuthate from Bi 2 O 3 and BaCO 3 via a two-step solid-phase heating method that, when sintered in oxygen, yielded a singlephase BaBiO 3 with monoclinic I 2/mm symmetry from high-resolution XRD, while XPS confirmed the presence of two valence states of bismuth: Bi 3+ and Bi 5+ . Optical spectroscopy revealed a direct bandgap of ∼2.2 eV and a possible indirect bandgap of ∼0.9 eV, which when combined with the activation energy for conduction of 0.25 eV (ac impedance spectroscopy) led Kumar et al [5] to infer a polaron-mediated conduction mechanism to prevail in BaBiO 3 .…”
Section: Introductionmentioning
confidence: 99%